The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/mcn.12979
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal overweight and obesity on milk composition and infant growth

Abstract: Overweight and obesity (OW/OB) impact half of the pregnancies in the United States and can have negative consequences for offspring health. Studies are limited on human milk alterations in the context of maternal obesity. Alterations in milk are hypothesized to impact offspring development during the critical period of lactation. We aimed to evaluate the relationships between mothers with OW/OB (body mass index [BMI] ≥25 kg/m2), infant growth, and selected milk nutrients. We recruited mother–infant dyads with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 58 publications
3
51
0
Order By: Relevance
“…There are increasing suggestions that, in addition to increasing the risk of pregnancy and neonatal complications, maternal overweight and obesity may be associated with changes in the macronutrient composition of human milk (HM) [8][9][10]. This is of clinical relevance, given the increasing number of studies that have reported associations between the levels of specific HM components, including fat, protein, and lactose in HM, as well as growth and fat deposition in the infant in the first 12 months of age [11,12]. Thus, changes in HM composition have the potential to promote weight gain and fat deposition in the infant [11], and thereby increase their risk of obesity and metabolic disease later in life.…”
Section: Introductionmentioning
confidence: 99%
“…There are increasing suggestions that, in addition to increasing the risk of pregnancy and neonatal complications, maternal overweight and obesity may be associated with changes in the macronutrient composition of human milk (HM) [8][9][10]. This is of clinical relevance, given the increasing number of studies that have reported associations between the levels of specific HM components, including fat, protein, and lactose in HM, as well as growth and fat deposition in the infant in the first 12 months of age [11,12]. Thus, changes in HM composition have the potential to promote weight gain and fat deposition in the infant [11], and thereby increase their risk of obesity and metabolic disease later in life.…”
Section: Introductionmentioning
confidence: 99%
“…( 24 ): Average age of lean mothers: 32.0 ± 4.1 years; Average age of obese mothers: 30.5 ± 5.7 years. ( 25 ): Average age of overweight-obese mothers: 29.9 ± 3.8 years (no statistically significant differences with lean group). ( 26 ): Maternal age in relation to BMI is not reported.…”
Section: Introductionmentioning
confidence: 91%
“…Infant growth up to 6 months of life was correlated with higher levels of dihomo-gamma-linolenic (20:3 n6-DGLA), adrenic (22:4 n-6), palmitic acids, conjugated linoleic isomers and reduced level of oleic acids in BM of overweight-obese mothers (25).…”
Section: Lipidsmentioning
confidence: 99%
See 2 more Smart Citations